Motivating Remote Working Employees for Improving Productivity and Job Satisfaction : The Case of SAP - Coelho, Tiago Furtado; Orel, Marko, 1986-; Petrů, Jaroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This study investigates employee motivation, productivity, and job satisfaction in a remote work environment in the post-pandemic era. Semi-structured interviews were conducted with twelve employees from SAP SE’s IT departments using qualitative research methods. The research applies Maslow's Hierarchy of Needs and Herzberg's Two-Factor Theory to analyze employees' perceptions of key motivational factors, including flexibility, autonomy, communication, social interaction, technology and infrastructure. Findings reveal that while flexibility and autonomy enhance motivation and productivity, challenges such as boundary management, social isolation, and disorganized communication tools hinder performance and satisfaction. Participants expressed a preference for hybrid work models, highlighting the need for occasional in-person interactions and improved home office setups. The study concludes with practical recommendations for managers to enhance remote working conditions by reducing mandatory office days, adopting trust-based management, promoting social engagement, standardizing communication tools, and supporting ergonomic home office setups. These findings provide critical insights for organizations implementing long-term hybrid work models, offering strategies to maintain employee motivation and organizational success.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses